Peruvian foreign policy in the new millennium: Continuity and change - St John, Ronald Bruce (2017)
Following almost three decades of political instability, economic uncertainty, and activist diplomacy, President Alberto Fujimori in the early 1990s returned a degree of economic and political stability to Peru. To restore the international standing of Peru, he also reoriented Peruvian foreign policy, modifying its direction, content, and tone. In the new millennium, successive Peruvian governments, from Alejandro Toledo to Ollanta Humala, have built on the initiatives introduced by Fujimori with a focus on traditional concerns, including sovereignty, territorial integrity, economic independence, regionalism, and continental solidarity. Notable for both continuity and coherence, Peruvian foreign policy after 2000 also evidenced a degree of pragmatism when an increasingly complex world called for new solutions to old problems.